USES AND EFFECTS OF MERCURY IN MEDICINE AND DENTISTRY - Iqbal, Kefi; Asmat, Maria (Journal of Ayub Medical College Abbottabad, 2012)
Mercury is known to be a toxic material with adverse effects on the body as claimed by so many researchers and always projected a negative aspect of this element. It is true that it may cause a several problems when it exceeds the safe limit but along with its negative image, mercury has been playing a positive role in the field of medicine and dentistry. It has many therapeutic uses including various medications, ointments, dental fillings, contact lens, cosmetics, paints as well as in different instruments like thermometer and sphygmomanometers. Mercury and its compounds used in dental practice may be responsible for release of mercury into the oral cavity. Compounds of mercury tend to be much more toxic than the element itself, and organic compounds of mercury (e.g., dimethyl-mercury) are often extremely toxic and may be responsible in causing brain and liver damage. Keywords: Mercury uses, Mercury toxicity, Dental amalgam, Elemental mercury, Dimethyl mercury